Biodiversity accounting: uncover environmental destruction in Indonesia. Issue 6 (5th October 2019) - Syarifuddin, Syarifuddin; Damayanti, Ratna Ayu
Abstract : Purpose: This study aims to reveal the impression which is delivered in the biodiversity report of local governments in South Sulawesi Province, Indonesia. It is crucial since the region has biodiversity that seems to get no specific attention in preserving its sustainability. Design/methodology/approach: Discourse analysis was used as a method to reveal fact and developing discourse. Analysis method to be developed was Eder cognitive discourse analysis, which was conducted by observing the narration in the biodiversity report. Findings: The findings of this study indicate that the informant's impression of the biodiversity report was made to attract investors by showing information related to local natural resources, thus allowing investors to exploit nature as needed. Nature and humans in the view of policymakers cannot be separated. Research limitations/implications: The implication of this research for further research is to focus more on the neutralization motives of the biodiversity reports preparers and the implications of community participation to save the environment. Practical implications: This study shows practice and policy of accounting in the organizational biodiversity as written in its report. Discourse and impression which are stated to the stakeholders need to be changed to show the seriousness of the region in biodiversity conservation. Originality/value: Many types of research studies have been conducted related to biodiversity accounting so far, but this paper views it from a different aspect. This paper discusses the intention and purpose of the report to show its spirit.